Assessment of the risks of occupational injury and illness for the position of welder - Elena Anda Botoc; Claudiu Babiş; Anișoara Habuc; George Mit; Andrei Dimitescu (Journal of Research and Innovation for Sustainable Society)
The paper presents a risk assessment and the action plan implemented for the welder position using the INCDPM method. The method allows the prioritization of risks according to their value and the efficient allocation of resources for labor protection. For the position analyzed by the welder, 37 risk factors were identified. The overall risk level calculated for the analyzed job is equal to 3.46, a value that places it in the category of jobs with an acceptable level of risk. As regards the distribution of risk factors on generating sources, the situation is as follows: 37.84% of the contractor's own factors; 5.41% factors specific to the workload and 37.84% factors specific to the means of production; 18.92% factors specific to the work environment. The purpose of the risk level assessment is to provide the possibility of knowing the real situation at each workplace, from the point of view of occupational safety, in order to take the most appropriate preventive measures for the given situation. In order to avoid or reduce occupational risks, occupational health and safety policies and procedures have been developed, in accordance with the Romanian legislation in force in conjunction with the applicable legislation of the European Union